Benefits and challenges of using smart meters for advancing residential water demand modeling and management: A review. (October 2015) - Cominola, A.; Giuliani, M.; Piga, D.; Castelletti, A.; Rizzoli, A.E.
Abstract: Over the last two decades, water smart metering programs have been launched in a number of medium to large cities worldwide to nearly continuously monitor water consumption at the single household level. The availability of data at such very high spatial and temporal resolution advanced the ability in characterizing, modeling, and, ultimately, designing user-oriented residential water demand management strategies. Research to date has been focusing on one or more of these aspects but with limited integration between the specialized methodologies developed so far. This manuscript is the first comprehensive review of the literature in this quickly evolving water research domain. The paper contributes a general framework for the classification of residential water demand modeling studies, which allows revising consolidated approaches, describing emerging trends, and identifying potential future developments. In particular, the future challenges posed by growing population demands, constrained sources of water supply and climate change impacts are expected to require more and more integrated procedures for effectively supporting residential water demand modeling and management in several countries across the world. Highlights: We review high resolution residential water demand modeling studies. We provide a classification of existing technologies and methodologies. We identify current trends, challenges and opportunities for future development.